Relationship between job demand and job resources on employees' work engagement in HVAC Industry in Malaysia - Rashifah, Kamaruddin (2013)
Employee engagement has become a contentious issue in the current economic climate, especially when companies lose critical talent in times when they most need to retain their knowledge capital if they are to remain competitive during an economic downturn. The present study was conducted to achieve two objectives: a) to examine the relationship between Job Demand (work load and work pressure) and work engagement; and b) to identify the relationship between Job Resources (performance feedback, support from colleagues and supervisory coaching) and work engagement. Therefore, the survey was conducted among 135 exempt staff of HVAC Industry in Malaysia. Data were gathered through questionnaires and was being analyzed by using Statistical Package for Social Science (SPSS) version 19. Furthermore, the result form the Pearson Correlation Coefficient shows that only Job Resources has a signification relationship with work engagement. which p<0.01. Anyway, job demands has negative relationship with work engagement but it is not significant since the p>0.05. Linear regression also shows that 76.8% of the variance of the perception of work engagement was explained by performance feedback, support from colleagues and supervisory coaching. Thus, it is crucial for the organization to put a great emphasize on the significant roles played by job resources to increased employees engagement in HVAC Industry in Malaysia